2021
DOI: 10.1016/j.atherosclerosis.2021.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-lowering therapy use in primary and secondary care in Central and Eastern Europe: DA VINCI observational study

Abstract: Background and aims: Central and Eastern Europe (CEE) is a largely understudied region, despite having the highest cardiovascular disease mortality in Europe. This analysis aimed to assess the proportion of patients in CEE who achieved their LDL-C goals based on individual cardiovascular risk recommended by the 2016 and 2019 European Society of Cardiology (ESC)/European Atherosclerosis Society (EAS) guidelines. Methods: The DA VINCI study was a cross-sectional observational study of primary and secondary preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 37 publications
4
60
0
1
Order By: Relevance
“…It is worth noting that it was not the target level of our study and, thus, there was some room for LLT optimization. This result improves that reported in the DA VINCI study; being one of the first comparative analyses evaluating 2019 risk-based goal attainment, showed that three-quarters of patients did not meet their 2019 LDLc goals ( 18 ).…”
Section: Discussionsupporting
confidence: 83%
“…It is worth noting that it was not the target level of our study and, thus, there was some room for LLT optimization. This result improves that reported in the DA VINCI study; being one of the first comparative analyses evaluating 2019 risk-based goal attainment, showed that three-quarters of patients did not meet their 2019 LDLc goals ( 18 ).…”
Section: Discussionsupporting
confidence: 83%
“…Over 40% of the population had elevated total blood cholesterol levels (defined as ≥ 5.0 mmol/L) or were taking hypolipemic medications. Overall, only 11% were at lipid target, and among very high-risk secondary prevention patients only 9% were at target [13]. Alcohol consumption and tobacco use are also very frequent.…”
Section: Pre-war In Ukrainementioning
confidence: 99%
“…Unfortunately, most of those affected are not aware of this, and many still ignore the risk associated with elevated cholesterol. Of the remaining patients, many are not treated optimally, and only about a quarter reach low-density lipoprotein cholesterol (LDL-C) targets, including only 17% of patients at very high CV risk [ 3 , 4 ].…”
Section: The Epidemic Of Lipid Disorders In Poland and Its Consequencesmentioning
confidence: 99%
“…Based on all of the data above, we strongly believe that inclisiran should be immediately available for very high-risk patients in Poland, as only 1/6 of these patients (17%) currently reach their LDL-C target [ 3 ]. We think that the available data from the ORION program on the high efficacy and unique safety (despite the indirect data on cardiovascular outcomes) are enough to add inclisiran to the existing drug program B-101 for PCSK9 inhibitors.…”
Section: Key Points For Reimbursement Of Inclisiran In Polandmentioning
confidence: 99%
See 1 more Smart Citation